A influência das transformações socioeconômicas e culturais na imagem da arquitetura: o caso do coreto da Praça Bernardino Bahia em Feira de Santana - Vieira, Priscilla Araujo (2023)
This research has as object of study the bandstand at Praça Bernardino Bahia, the first of three built in the city of Feira de Santana in the first decades of the 20th century. In yours more than one hundred years old, the bandstand at Praça Bernardino Bahia was modified according to social ideologies and the urban landscape around them have been changing, so this research aimed to understand how socioeconomic issues contributed to the changes in the design of this gazebo. For this, this study was limited between the years of 1915, its implementation, until the year 2020. The method followed to obtain the results desired was the documental analysis, since it was observed that the direct contact with the object of study, the use of images, field visits, informal conversations, official records and popular experiences were the most appropriate means to achieve the objectives imposed on the search. In this process, drawing was used as the main instrument for the recognition of the physical changes to the bandstand at Praça Bernardino Bahia; with every stroke made, we sought to perceive what was new in the figure of the bandstand and, in this way, register the different versions that this urban equipment had until 2020. In order to understand better the object of study, discussions were raised regarding its architectural style eclectic and the influence of everyday life in the city for changes in its design, as well as the social transformations and the relationship between this bandstand and the collective memory of the townspeople. At the course of the research, it was seen that, due to its importance in the history of Feira de Santana, the bandstand at Praça Bernardino Bahia was listed, recognized as heritage city ​​culture. However, it was verified that this action was not enough for the conservation of the good, nor for its valorization in the current society of Feirense.